2016
DOI: 10.1186/s13000-016-0458-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of TERT promoter mutations and ALK rearrangement in thyroid cancer patients with a high prevalence of the BRAF V600E mutation

Abstract: BackgroundMutations in the TERT promoter, ALK rearrangement, and the BRAF V600E mutation are associated with aggressive clinicopathologic features in thyroid cancers. However, little is known about the impact of TERT promoter mutations and ALK rearrangement in thyroid cancer patients with a high prevalence of BRAF mutations.MethodsWe performed Sanger sequencing to detect BRAF V600E and TERT promoter mutations and both immunohistochemistry and fluorescence in situ hybridization to identify ALK rearrangement on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 49 publications
1
58
1
1
Order By: Relevance
“…Consistent with previous studies, the present study on Chinese patients found a TERT mutation prevalence of 22.73% (15/66) in patients with distant metastatic DTC, with C250T mutation also being less frequent (2/15, 13.33%). In contrast, the incidence of TERT mutation in patients with distant metastatic DTC is slightly more common in South Korea (12/30, 40%) and Italy (14/43, 33%) (15,25). Our data also showed that besides being associated with radioiodine refractory status, TERT mutation in patients with distant metastatic DTC was associated with larger tumor size, older age, and greater likelihood of BRAF mutation coexistence, in agreement with previously published data (15).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, the present study on Chinese patients found a TERT mutation prevalence of 22.73% (15/66) in patients with distant metastatic DTC, with C250T mutation also being less frequent (2/15, 13.33%). In contrast, the incidence of TERT mutation in patients with distant metastatic DTC is slightly more common in South Korea (12/30, 40%) and Italy (14/43, 33%) (15,25). Our data also showed that besides being associated with radioiodine refractory status, TERT mutation in patients with distant metastatic DTC was associated with larger tumor size, older age, and greater likelihood of BRAF mutation coexistence, in agreement with previously published data (15).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, research in Western countries has shown lower frequencies of the BRAF V600E mutation in patients with PTC . This may be associated with different genetic backgrounds, possibly related to molecular genotypes for the other oncogenic mutations, although this remains unclear …”
Section: Discussionmentioning
confidence: 92%
“…Full-text of the remaining 40 studies were further evaluated, and 22 studies with 4,907 patients were ultimately included in this meta-analysis 1217,22,23,27,3042. All the 22 studies reported the frequency of TERT promoter mutations,1217,22,23,27,3042 18 studies were available for analyzing the clinicopathological features and prognostic significance,1417,22,23,27,3133,3542 15 studies investigated the relationship of TERT promoter and BRAF V600E mutations,13,15,16,22,23,27,3337,3942 and six of them evaluated the synergetic effect of both mutations 15,24,25,35,37,41. According to the NOS system, 11 studies were classified as high-quality and the other 11 were mid-range.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the coexistence of BRAF V600E and TERT promoter mutations indicated more aggressive tumor and worse prognosis, and the influence of TERT promoter mutations seemed to be more significant than BRAF V600E mutation. The mechanism underlying the synergetic effect of BRAF and TERT promoter mutations remains uncertain 15,24,25,29,30,39,50. Vinagre et al and Bullock et al demonstrated that BRAF and TERT promoter mutations can increase the expression of each other,17,37 which may be achieved by activation of MAPK pathway and regulation of ETS transcriptional factors 50.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation